STRUGGLE FOR LIFE IN THE CURIOUS CASE OF BENJAMIN BUTTON (2008) DIRECTED BY DAVID FINCHER: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - MARTADI, DIANTO ARIF (2010)
The major problem of this study is to elucidate the struggle for a better life of Benjamin Button reflected in David Fincher's The Curious Case of Benjamin Button. The objectives of the study are; to analyse the structural elements of the movie and to analyse the character of Benjamin Button based on individual psychological perspective. In conducting this study, the researcher uses qualitative research in which the data are based on primary data the movie David Fincher's The Curious Case of Benjamin Button itself. While secondary data are David Fincher's biography and other data which is related with the research. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, casting, plot, setting, point of view, theme, mise en scene, cinematography, sound, and editing are related to each other and form the unity into good quality of a movie. Second, based on the individual psychological analysis, there is close relation between the movie production and the psychological view underlying it. The writer finds that Benjamin Button's struggle for a better life leads him to an autonomous personality that has a great self confident in life. This movie also teaches that someone should sacrifice for their dreams.